PENERAPAN METODE WATERFALL DALAM PERANCANGAN SISTEM INFORMASI E-LEARNING BERBASIS WEB PADA MADRASAH TSANAWIYAH (MTS) AL-WUSHO RUMAH SETIA RUMAH SETIA - Rahmad Ardhani; Muhammad Misbahul Munir; Aisyah Mutia Dawis (Journal of Innovation And Future Technology (IFTECH), 2023)
Education is one of the benchmarks for the progress of a nation. One way to advance education is to follow technological developments. And technological developments are currently developing so rapidly, one of the technologies that exist in the world of education today is E-Learning. E-Learning is a form of technological progress that can be utilized effectively and efficiently for the learning process. E-Learning is an education system that uses electronic applications to support the development of teaching and learning activities using internet media. (1) Madrasah Tsanawiyah (MTs) Al-Wusho Rumah Setia is one of the schools in Sukoharjo Regency. At Madrasah Tsanawiyah (MTs) Al-Wusho Rumah Setia the learning process is still traditional, namely the teaching and learning process between teachers and students is only carried out in class meetings and attendance using manual recording. Based on these conditions, an information system is needed that can facilitate the attendance process and can monitor teachers so that they can produce accurate reports. Utilization of information technology today can be used as a solution to overcome these problems. Therefore, as a solution to the problems above, this research provides a solution for making E-learning Information System Design. The National Training and Simulation Association reports that retention of material after learning through e-learning can reach 25-60%, whereas through classical learning it is only around 8-10%.